2003
DOI: 10.1016/s0736-0266(03)00100-1
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic differentiation of mesenchymal progenitor cells encapsulated in ultrahigh‐viscosity alginate

Abstract: One major problem of current cartilage repair techniques is that three-dimensional encapsulated mesenchymal progenitor cells frequently differentiate into hypertrophic cells that express type X collagen and osteogenic marker genes. Studies on wild-type cells of murine mesenchymal C3H10T1/2 progenitor cells as well as on cells transfected with cDNA encoding for bone morphogenetic protein (BMP)-2 or -4 in alginate revealed that the formation o f markers for osteogenesis and chondrogenic hypertrophy apparently de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 60 publications
(56 reference statements)
4
84
0
Order By: Relevance
“…The high collagen type X expression is in accordance with results obtained from murine MSCs. 13 We further observed that the age of the donors correlated to their ability to produce matrix, with a high matrix production in the younger donors. MSCs A produced almost no cartilage-like matrix compared to articular chondrocytes and MSCs B .…”
Section: Discussionmentioning
confidence: 55%
“…The high collagen type X expression is in accordance with results obtained from murine MSCs. 13 We further observed that the age of the donors correlated to their ability to produce matrix, with a high matrix production in the younger donors. MSCs A produced almost no cartilage-like matrix compared to articular chondrocytes and MSCs B .…”
Section: Discussionmentioning
confidence: 55%
“…Studies involving embryonic stem cells and mesenchymal progenitor cells also have demonstrated the beneficial effect of BMP-4 on chondrogenic differentiation in vitro (30,31,46). Other research groups have used the culturing of cells in a micromass pellet culture system as an assay for chondrogenesis, and this approach appears to be optimal for assessing the chondrogenic differentiation of mesenchymal stem cells (35,(41)(42)(43).…”
Section: Bmp-4 and Mdscs In Cartilage Repairmentioning
confidence: 99%
“…Many researchers have chosen to focus on the study of cellseeded matrices in an effort to engineer synthetic cartilage in vitro for implantation in vivo. The use of cells suspended in fibrin glue instead of solid grafts enables the suspended cells to settle even in narrow clefts, and fast-forming clots are able to prevent any initial displacement (31). Research has demonstrated that fibrin glue has no adverse effects on cell viability 440 KURODA ET AL and is a suitable matrix for applications designed to promote chondrogenesis (49).…”
Section: Bmp-4 and Mdscs In Cartilage Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore cells behave in a more natural way, retaining more physiological functionality, if they have three dimensional environments. Chondrocytes, for example, produce cartilage typical collagen II only when they are cultured in three dimensional environments (Steinert et al 2003). The increasing interest of biomedicine in cell-matrix constructs promotes the development of high throughput culture techniques (Tendulkar et al 2012) and increases the interest in cryopreservation of these constructs for retrospective investigations, pooling and stock keeping (Malpique et al 2010;Zhang et al 2009).…”
Section: Introductionmentioning
confidence: 99%